Coping A Philosophical Guide - Bovens, Luc (Open Book Publishers, 2021)
Coping is a collection of philosophical essays on how we deal with life's challenges. We hope for better times, but what is hope, and is it a good thing to hope? How do we look back and make sense of our lives in the face of death? What is the nature of love, and how do we deal with its hardships? What makes for a genuine apology, and is there too much or too little apologizing in this world? Can we bring about changes in ourselves to adapt to our circumstances? How can we make sense of all the good advice-such as, count your blessings, don't cry over spilled milk-that people have on offer? Coping is a perfect companion text for a moral psychology course, a resilience course, or part of an ethics course. The material is written for readers who are new to philosophy and progresses in short self-contained sections. It draws on literature, music, podcasts, and news items. Each chapter has questions for discussion or essay writing and suggestions for material to explore the topic further.